Mathematical Literacy of Junior High School Students in Kecamatan Tampan Kota Pekanbaru in Geometry - Siregar, Syarifah Nur; Solfitri, Titi (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
This study aimed to determine the mathematical literacy (reasoning and communication of mathematics) of junior high schoolstudents in KecamatanTampan Kota Pekanbaru in geometry. The research instrument used instruments PISA 2012 with space and shape content translated into Indonesian. Overall, the test consists of 14 items with the nine themes. The population in this study are student at class IX of SMPN 20 and SMPN 23 Pekanbaru. Randomly selected one class from each school in order to obtain a sample of 74 people. The results showed that students mathematical literacy is still low with an average score of 46.90 and a standard deviation of 15.15. For aspects of mathematical reasoning abilities, students tend not able to use patterns and relationships to analyze mathematical situations, provide explanations using models, facts, attributes, and relationships, as well as estimating the answer and the solution process. For aspect of communication, students tend not able to connect real objects, drawings, and diagrams into mathematical ideas.